Pengaruh Latihan Small Sided Games Terhadap Ketepatan Short Pass Kaki Bagian Dalam Pada Pemain Rajawali Football Club U-14 Kota Semarang 2023 - Noor Ahmad; Tri Nurharsono; Martin Sudarmono (Indonesian Journal for Physical Education and Sport, 2024)
This research based on insufficient quality passing especially short pass of the legs in when their every move is passing the basic technique u-14 poor passing.This study attempts to find out the accuracy of passing from the small sided games improve the quality of the legs in the short pass u-14 eagle fc.The results of the study with this t ( paired t ) tests show the short pass of the legs in having the significance of t count ( 2-tailed ) & gt; t table ( 1,79 & gt; 1,67 ) hypothesis accepted.A small sided games can improve the accuracy of short pass of the legs in.While in short pass of the legs in football also have significant value of t count ( 2-tailed ) & gt; t table ( 25,59 & gt; 1,69 ) received the hypothesis.A small sided games will increase the quality of passing football player player u-14 rawajawali semarang city fc.